Tumbling fluidized-bed process parameters affecting quality of biopolymer coating on surface of pristine urea particles - Azeem, B. (Elsevier B.V., 2017)
When pristine urea particles are subjected to spray coating in a fluidized bed, the frequency of substrate particles to come across the spray zone changes due to various hydrodynamic factors of the fluidized bed giving rise to preferential coating. The heterogeneity of coating film on the surface of urea particles results in poor coating quality which ultimately affects the controlled-release properties of the coated product. In this study, the effect of tumbling fluidized bed process parameters is studied on coating quality and the Response Surface Methodology is employed for the optimization of process parameters for better results. In case of coating uniformity w.r.t. coefficient of variance (CV) of coating thickness, atomizing air pressure appears as the most influential parameter. The best coating uniformity in this case is achieved at 2.25 bar of atomizing pressure. The lowest and highest values of atomizing pressure resulted in higher CV of coating thickness. In case of coating uniformity w.r.t. change in coating mass, coating time appears the most influential parameter. Coating mass increases linearly with coating time. For coating uniformity in terms of CV of size distribution, atomizing pressure and fluidizing gas temperature are the most influential parameters. The best coating uniformity is witnessed at 85 °C and 1.90 bar. The optimum values of process parameters and response objectives can be used to scale-up the unit used. © 2017 Elsevier B.V.